Detection of Rotavirus and Adenovirus diarrhea in children below five years, in Dakshina Kannada District, a coastal region of Karnataka State, India - Anup Kumar Shetty; Faizan Mohammad Kalekhan; Sibin Jose Muthiravalapil; Rekha Boloor; Beena Antony (Wolters Kluwer Medknow Publications, 2014)
Context: Diarrheal disease is the second largest cause of death of children under 5 years. Viral diarrhea is most common which is usually caused by Rotavirus followed by enteric Adenovirus. Rotaviruses are responsible for approximately 527,000 deaths mainly in low-income countries of Africa and Asia. There is limited number of studies done on viral diarrhea in this coastal belt. Aim: To determine the prevalence of Rotavirus and Adenovirus diarrhea among children below 5 years of age and its epidemiological importance in this coastal region of Karnataka State, India. The impact of factors like socio-economic status, drinking water, and Rotavirus immunization status that can contribute to the disease were also evaluated and recommendations are formulated for disease prevention. Materials and Methods: Children below 5 years of age with history of diarrhea, vomiting and fever of less than 3 days were included in this study. The sample size was 35. General physical examination, clinical findings and other details like socio-economic status, personal hygiene, growth milestones and family income were also recorded. A commercial Rotavirus and Adenovirus antigen detection kit was used to detect the presence of Rotavirus and Adenovirus antigen from the stool sample. Results: Out of 35 patients screened, 25 (71.43%) patients were negative for both Adenovirus and Rotavirus, 10 children (28.57%) were positive for Rotavirus and no patients were positive for Adenovirus. Severe dehydration, fever, loose stools and vomiting were the commonest symptoms seen in Rotavirus positive children. The highest incidence of infection with Rotavirus was seen among 7-12 months age group. Children whose stool was positive for Rotavirus used public water supply. Conclusions: Rotavirus is an important cause of diarrhea in children below 5 years in this coastal region. A simple, rapid immunochromatography test is useful and economical tool to simultaneously detect and screen Adenovirus and Rotavirus. Low socioeconomic state and unsafe water supply contributes to diarrheal disease.